Massive burn > 90% of body surface – case report - Hys, Michał; Kempisty, Jakub; Budny, Agnieszka; Baranowska-Kempisty, Katarzyna; Rutyna, Rafał (Journal of Education, Health and Sport, 2019)
Severe burns are life-threatening injuries very difficult to heal. Multidisciplinary treatment is necessary due to complicated pathophysiological cascades induced by massive tissue destruction. Children and elderly people are especially endangered in being burnt. We present case of 73 years old woman with massive burn injury of >90% body surface.